SOCIAL AND EMOTIONAL LEARNING IN TEACHER PREPARATION: PRE-SERVICE TEACHER WELL-BEING - Abdullayeva Munojot Mukhtorovna (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This article explores the integration of social and emotional learning (SEL) into pre-service teacher education and its significance for promoting teacher well-being. Recognizing the emotional challenges faced by novice educators, the study highlights how embedding SEL competencies—such as self-awareness, emotional regulation, and relationship skills—can enhance resilience, reduce stress, and foster a positive classroom environment. Despite its promising potential, current teacher preparation programs often lack systematic inclusion of SEL components. The paper reviews existing frameworks, discusses the benefits and challenges of implementation, and offers recommendations for integrating SEL into teacher training to support the mental health and professional development of future educators.